Metaphors for interdependence: Fazang's Buddhist metaphysic - Jones, Nicholaos (Oxford University Press, 2025)
"Fazang is one of the most celebrated and influential thinkers in the history of Chinese Buddhist philosophy. Metaphors for Interdependence is a rigorous and accessible exploration of Fazang's metaphysical theories, focusing in particular on his vision of reality as a realm in which everything is interdependent and interpenetrating. Fazang explains this vision with metaphors about Indra's net, coin counting, and a building. The result is the systematic articulation of metaphysics for the Huayan tradition of Buddhism. Nicholaos Jones reconstructs the intellectual background that gives meaning to Fazang's theories. He provides vivid examples to help readers understand Fazang's distinctive insights. Jones also develops incisive interpretations of Fazang's metaphors by examining how Buddhist optical theory, breathing meditation, and ancient Chinese architecture inform Fazang's theorizing. By situating Fazang's insights within broader traditions of Buddhism, Metaphors for Interdependence challenges facile conceptions of interdependence while inviting readers to reconsider a range of common metaphysical assumptions"--